A qualitative study of health professionals' views on the holding of children for clinical procedures: Constructing a balanced approach. (March 2019) - Bray, Lucy; Ford, Karen; Dickinson, Annette; Water, Tineke; Snodin, Jill; Carter, Bernie
Children undergoing clinical procedures can experience fear, uncertainty, and anxiety which can cause them to become upset and resist procedures. This study aimed to capture an international perspective of how health professionals report they would act if a child was upset and resisted a procedure. An online questionnaire, distributed through network sampling, used three vignettes to elicit qualitative open text responses from health professionals. Seven hundred and twelve professionals participated, resulting in 2072 pieces of text across the three vignettes. Many professionals reported that they would use distraction and spend time to inform and engage children in making choices about their procedure. However, most professionals indicated that if a child became uncooperative they would hold or instruct the holding of the child in order to get the procedure done 'as quickly as possible'. The findings demonstrate that professionals experience difficulty in balancing the different agendas, rights and priorities within the momentum which can build during a clinical procedure, often resulting in the child's voice and rights being undermined. A more balanced approach could be facilitated by a 'clinical pause' that would equip professionals with the time to consider children's expressed wishes and explore alternative approaches to holding.